2006
DOI: 10.1677/jme.1.01921
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of vascular endothelial growth factor expression and blood vessel remodelling in pig ovarian follicles during the periovulatory period

Abstract: Vascular endothelial growth factor (VEGF) expression pattern and blood vessel remodelling were evaluated during the transition from the preovulatory follicle to the corpus luteum (CL). To this end, prepubertal gilts were treated with equine chorionic gonadotrophin (eCG) to collect preovulatory follicles (60 h after eCG) and with human chorionic gonadotrophin (hCG) to obtain periovulatory follicles 18 h and 36 h later. The VEGF mRNA content was analysed by in situ hybridization, while protein localization in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(81 citation statements)
references
References 55 publications
0
80
1
Order By: Relevance
“…Similar to other molecules, VEGFA could be included among the signals involved in the bidirectional control of oocyte-follicle function (Diaz et al 2007, Hutt & Albertini 2007, by guaranteeing that follicle development can be synchronized with the growth of the metabolically active germinal cells. Even if it has been demonstrated that there are also post-transcriptional and post-translational mechanisms involved in VEGFA expression in the ovary and other tissues (Hazzard et al 1999, Neufeld et al 1999, Martelli et al 2006, in this research all preantral follicles showed a relationship between VEGFA mRNA and protein production. In fact, the follicles and the oocytes that expressed the transcript were also positive Vasculature during preantral follicle development 51 to the related protein.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Similar to other molecules, VEGFA could be included among the signals involved in the bidirectional control of oocyte-follicle function (Diaz et al 2007, Hutt & Albertini 2007, by guaranteeing that follicle development can be synchronized with the growth of the metabolically active germinal cells. Even if it has been demonstrated that there are also post-transcriptional and post-translational mechanisms involved in VEGFA expression in the ovary and other tissues (Hazzard et al 1999, Neufeld et al 1999, Martelli et al 2006, in this research all preantral follicles showed a relationship between VEGFA mRNA and protein production. In fact, the follicles and the oocytes that expressed the transcript were also positive Vasculature during preantral follicle development 51 to the related protein.…”
Section: Discussioncontrasting
confidence: 60%
“…In addition, morphological adjustments of the vascular supply may be crucial to regulate follicle growth and differentiation, although such a cause effect has yet to be established (Redmer & Reynolds 1996, Barboni et al 2000, Berardinelli et al 2002. In particular, during the final antral stages, follicle growth is coupled with an increased blood vessel area , close to ovulation, changes its organization into a mature vascular network (Martelli et al 2006). In fact, until the periovulatory phase, the vascular network is represented by capillaries that, a few hours before ovulation, become covered by pericytes, and new large blood vessels appear in the follicular wall (Zimmermann et al 2003, Martelli et al 2006.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After 2, 5 and 9 days, the medium was collected and the cells fixed in acetone:methanol (1:1) at room temperature for 5 min. The endothelial cells were then immunostained using VWF as an established endothelial cell marker in order to assess the formation of tubule-like structures over time (Al-zi'abi et al 2003, Martelli et al 2006.…”
Section: Tissue Collection and Luteal Angiogenesis Culture Systemmentioning
confidence: 99%